Media Political Economy: Vincent Moscow's Commodification in Tempo's Bocor Alus Politik Podcast - Arisandha; Atnan, Nur; Akbari Fitriawan, Rana; Retno Wulan, Roro; Yanda, Fikri (Jurnal Riset Komunikasi (JURKOM), 2026)
Tempo has transformed its news presentation strategy by developing more engaging video and audio content, particularly through the Bocor Alus Politik podcast. The commodification process within this podcast is intriguing to examine from a media political economy perspective. This study analyzes the implementation of Vincent Mosco’s theory of commodification covering content, audience, and labor in the Bocor Alus Politik podcast on YouTube. Using a qualitative approach and content analysis, the research explores how investigative journalism is repackaged into commercially viable digital products. The findings show that content commodification occurs through casual formats, provocative titles, and branding strategies that enhance exchange value while promoting Tempo’s premium subscription services. Audience commodification is reflected in the transformation of viewers into measurable assets through data extraction, watch time, and engagement metrics such as likes and shares that strengthen algorithmic visibility. Labor commodification reveals that journalists’ expertise, time, and reputation are capitalized as intangible assets to boost digital performance, often blurring the boundary between editorial independence and commercial demands. This study highlights the tension between economic sustainability and journalistic integrity in the digital platform era.